Calyhedins I–VI: Resin glycosides from the rhizomes of Calystegia hederacea. (October 2021) - Ono, Masateru; Yuhara, Nobuyoshi; Shimohara, Takaaki; Matsubara, Souta; Yasuda, Shin; Tsuchihashi, Ryota; Okawa, Masafumi; Kinjo, Junei; Zhou, Jian-Rong; Yoshimitsu, Hitoshi; Nohara, Toshihiro
Abstract: Six previously undescribed resin glycosides, calyhedins I–VI, were isolated from the rhizomes of Calystegia hederacea Wall., which are the first genuine resin glycosides isolated from C. hederacea . The structures of calyhedins I–VI were determined based on spectroscopic data and chemical evidence. All the compounds have macrolactone structures (jalapins), and their sugar moieties were partially acylated by five organic acids. Calyhedins I, II–V, and VI have 27-, 28-, and 23-membered rings, respectively, and calyhedins IV–VI are the first jalapins with a sugar chain consisting of seven monosaccharides. Additionally, the cytotoxic activity of calyhedins II and III toward HL-60 human promyelocytic leukemia cells was evaluated. Both compounds demonstrated almost the same activity as the positive control, cisplatin. Graphical abstract: Image 1 Highlights: Six undescribed resin glycosides were isolated from Calystegia hederacea. These are the first genuine resin glycosides isolated from C. hederacea. All six compounds have a macrolactone structure. Three of the compounds have a sugar chain consisting of seven monosaccharides. Two compounds demonstrated cytotoxic activities toward HL-60 cells.